Study on Corrosion Behavior of A106 Carbon Steel in Dense-Phase CO2 Environment - YU Zhixia, ZHANG Guoqing, LI Yan, WAN Mingqi, WANG Zhi, WANG Yuesong, JIN Zhengyu, LIU Haixian, CHEN Jiongming, LIU Hongwei (Cailiao Baohu)
The corrosion problem of metal materials in supercritical-dense phase CO2 environment is a key factor influencing Carbon Capture,Utilization and Storage (CCUS) technology.However, the corrosion behavior in the micro-water environment with strong corrosive ions is still in need of further investigation.This study focused on investigating the corrosion behavior of A106 steel in dense-phase (liquid) CO2 environments.A high-pressure autoclave was employed to simulate the dense-phase CO2 conditions, while weight loss measurements, scanning electron microscopy (SEM), X-ray diffraction (XRD) and super-depth-of-field 3D microscopy were utilized to systematically examine the effects of micro-water content (200, 1 000, 1 500, 2 000, 2 500 and 3 000 μL/L) on the corrosion behavior of A106 steel.Results showed that in dense-phase CO2 environments, A106 steel exhibited its maximum uniform corrosion rate of 0.086 7 mm/a at a water content of 3 000 μL/L.An uneven ferrous carbonate corrosion product film formed on the specimen surface, creating favorable conditions for localized corrosion development, with the maximum pitting rate reaching 0.548 mm/a.Furthermore, water content was the critical factor affecting metal corrosion in dense-phase CO2 environments, and under the conditions of 25 ℃and 10 MPa, water and CO2 become mutually soluble.In the micro-water environment, water primarily existed in a dissolved state within the liquid CO2 phase,and trace amounts of free water accumulated on the specimen surface, forming discontinuous liquid films or droplets that accelerated the corrosion of A106 steel.